ANALISIS TINGKAT KESEHATAN KOPERASI SIMPAN PINJAM SIDA MEGAR CILACAP - Fatih, Faiz Al; Zaidan, Naufal Ali; Wiratno, Adi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2024)
This study aims to evaluate the health level of Koperasi Simpan Pinjam Sida Megar in Cilacap Regency during the 2021-2023 period. The assessment is based on the indicators stipulated in Regulation No. 20/Per/M.KUKM/XI/2008 by the Ministry of Cooperatives and SMEs, which include aspects of capital, asset quality, management, efficiency, liquidity, independence, and cooperative identity. The data used are financial statements of the cooperative, and a descriptive quantitative analysis was employed to generate evaluation scores. The results indicate that the cooperative achieved a fairly healthy status for most indicators but faced challenges in liquidity, independence, and member participation. These findings provide important insights for cooperative managers to improve performance and operational sustainability.should inform the readers briefly about the manuscript’s purpose, methods, findings, and values.